Analysis and Optimization of Crossbeam of Gantry Machining Center - Yingjun Guan; Lili Ren; Jianwei Sun; Deqiang Mu (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Finite element model of crossbeam of GMCU2060 gantry machine center is proposed, the static and dynamic stiffness is analyzed by using finite element analysis. The weak link of the crossbeam is discovered and a modification scheme is put forward for the design of the crossbeam structure. The analysis shows that the maximum deformation of the improved crossbeam is decreased to 0.03 mm and the first order natural frequency is increased to 116 Hz.